Who cares about performance? Art, politics and education in focus (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This is a critical review of the book Performance by Diana Taylor, a North-American researcher well-known for her studies in Performance in dialogue with Latin American issues. Translated and introduced by Leda Maria Martins, the book is divided into nine chapters and provides an overview of the main discussions related to the topic, including dissonant views about it. Although the author’s analysis is summarily situated in the fields of Art and Politics, this review points to possible articulations between such fields and Education, drawing mainly from Paulo Freire´s studies.
Keywords: performance; art; politics; education